Identification of fungal disease, the causal agent of postharvest fruit rots disease on papaya (Carica papaya L.) - Azmi, Nor Atikah (2017)
Fruit rot of papaya (Carica papaya L.) is a postharvest disease in Malaysia. Symptoms of fruit rot, commonly appear during storage are characterized as dark with a wide margin of watery tissue and a surface wrinkled owing to the eruption of the pycnidia. This results in economic loss for fresh market of up to 90% and reduced the domestic market as well for export industry. Morphological criteria such as cultural, conidial and appressorial characters were used to differentiate taxa into species complexes, but cannot separate Lasiodiplodia species within a complex. To date, the genus had 30 species known from culture infecting host plants that are more than 500 hosts. Lasiodiplodia theobromae have been identified as a species causing fruit rot on papaya within the Lasiodiplodia species complex using ITS sequence data and phylogenetic species of Lasiodiplodia species causing fruit rot on papaya was constructed. The morphological observations of Lasiodiplodia theobromae was based on characters such as host preference, conidial size and shape, growth rate in culture, colour of the cultures, presence and absence of setae as well as teleomorph. Here, the identity of causal agent of fruit rot of Carica papaya has been confirmed with the application DNA sequencing of ITS regions of the isolates. Through BLAST finding, the identity of the isolates is 99 % and consisted of 547 bp. By combining DNA-based molecular technique with morphological evidence, recent studies on papaya will improve our understanding of the Lasiodiplodia species complex causing fruit disease on papaya.